1989
DOI: 10.1063/1.101271
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of SiC for crystalline/amorphous pattern fabrication

Abstract: A 100nm patterned xray mask technology based on amorphous SiC membranes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 6 publications
4
16
1
1
Order By: Relevance
“…Because of the strong absorption in the energy range of the laser wavelength, the penetration depth of the laser beam is strongly decreased (typically the penetration depth decreases to a few tens of nanometer in heavy coloured sample 30,31 ) and the Raman signature of the red Cu 0 n samples is essentially a surface phenomenon. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the strong absorption in the energy range of the laser wavelength, the penetration depth of the laser beam is strongly decreased (typically the penetration depth decreases to a few tens of nanometer in heavy coloured sample 30,31 ) and the Raman signature of the red Cu 0 n samples is essentially a surface phenomenon. 2.…”
Section: Discussionmentioning
confidence: 99%
“…21 It was found that the laser penetration decreases when the electronic absorption increases and is expected to be only a few hundred nanometres (or even less) in carbon-containing materials. Resonant Raman spectra are expected from SiC fibre carbon moieties with all of our laser lines and, as a result, the Raman cross-section of carbon is much higher than that of SiC.…”
Section: Analysed Volumementioning
confidence: 99%
“…Fig. 2a compares the absorbency profile of powdered Hi-Nicalon fibers with electronic absorption tails for single crystals of bSiC [41 ± 43] and for a-SiC [44]. Due to the fast sedimentation in the inert solvent that was used, the absorbency level is arbitrary and only lineshape makes sense: Hi-Nicalon ªSiCº fibers exhibit a strong absorption in the full energy range, as observed for amorphous, carbon-rich, SiC films (see Fig.…”
Section: Carbon Resonancementioning
confidence: 99%
“…(a) Absorptionskurve von pulverfo Èrmigen SiC-(Hi-Nicalon)-und Kohlenstoff-(hochkristallines FT700)-Fasern, die in CCl 4 dispergiert sind. Die Werte fu Èr den Absorptionskoeffizient (cm À1 Einheit) sind denen fu Èr reines a-SiC [44] und b-SiC [41 ± 43] u Èberlagert; (b) Lichtpenetration in amorphen SiC-Filmen, nach Derst et al[44] …”
unclassified